(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This special issue examines when and how information could be utilized to enhance governance and public service delivery in rural regions, against the backdrop of an exponential expansion in access to information over the previous two decades. This evaluation’s objectivity will allow us to examine how the organization’s service provision affects its overall governance. Both the federal and state governments are responsible for making these laws workable and putting them into effect. The term ‘citizen involvement’ refers to the method by which citizens have a say in and are accountable for the choices, resources, and programmed that impact them in the name of development. In the public sector, good governance is meant to provide a standard for how things should be run in order to promote more transparency and accountability. The Pune Municipal Corporation Governance and service delivery is studied in this paper.